Transformative Education Curriculum: Developing Nahdlatul Wathan Warriors in Maulana II's Era - Thohri, Muhammad; Harapandi (Cendekia: Kependidikan dan Kemasyarakatan, 2024)
The purpose of this research is to investigate the transformative education curriculum at Pondok Pesantren Syaikh Zainuddin Nahdlatul Wathan (NW) in Anjani and provide insights into its implementation and impact under the leadership of Ummuna Hajjah Siti Raihanun Zainuddin Abdul Madjid and Maulana Syaikh II. This research is essential as it delves into the transformative education curriculum at Pondok Pesantren Syaikh Zainuddin NW in Anjani. This research employed a descriptive qualitative approach. The data was gathered through participatory observation, in-depth interviews, and documentation. It provides a systematic analysis of the curriculum's role. The findings reveal the positive outcomes, such as improved access to education, equal distribution of opportunities, and societal transformation, aligning with the broader vision of Nahdlatul Wathan. This research contributes to the understanding of transformative education and offers methodological insights for studying similar phenomena, emphasizing the crucial role of educational institutions in shaping societies and realizing organizational goals.